Public Participation by Resident Associations in Local Authorities Administration in Kuching District, Sarawak, Malaysia - Leha Saliman, Ahi Sarok, (Social Science Learning Education Journal, 2017)
The purpose of this article is to discuss  public participations by Residents Association  in local authorities administration in Kuching District, Sarawak, Malaysia. This article also discusses the structure of the Resident Associations and the various activities these structures organised which benefitted the communities living in the neighbourhood. All three local authorities  namely the DBKU, MBKS and MPP indicated that Resident Associations  play an important role to create mutual relationship with the public towards better local authorities administration.  In addition, it highlighted the  roles played by the Resident Associations in  three local in promoting public participation through various  programmes and activities.   Resident Associations also play an important in preventing crimes by improving security at their neighbourhood, increasing vigilance, creating and maintaining a caring community.  They also play a vital part in the local government administration especially in maintaining cordial relationship between the residents and the local authorities. Finally this article discuss the programmes and activities implemented by the Resident Associations in collaboration with the local authorities. Amongst the activities discussed in this article are safety and crime prevention programmes, recycling programme, recreational and sports activities, community  services or gotong-royong, and other programmes that are beneficial to communities living in the neighbourhood. Key Words: Residents Association, public participation and local authorities, Sarawak.